A study on the severe crazing phenomenon of the PMMA canopy under prolonged exposure to tropical climates. (November 2021) - Kim, Ik-Sik; Cho, Hwanjeong; Sohn, Kyung-Suk; Kim, Kyungwoo; Kim, Sinkon
Highlights: The severe crazing phenomenon in the PMMA canopy of the light aircraft operated in the tropics for more than seven years was investigated. The crazing resulted from the chain scissions of ester pendant groups (COOCH3 ) and partial or continuous monomers [CH = C(CH3 )COOCH3 ] from the main PMMA chain via photolysis. Numerous voids (defects) by chain scissions in nanometers functioned as the initial points of crazing. Crazes continued to grow symmetrically from the starting points of voids to both tips in micrometers under the environmental thermal stress before rupture. These crazes proceeded in the same two aligned directions as the internal tension stress formed during the canopy manufacturing process. Abstract: The severe crazing occurred in the poly(methyl methacrylate), PMMA canopy of the light aircraft operated in the tropics for more than seven years. The crazing phenomenon was investigated to identify the root cause and the mechanism for the formation of the crazing. The crazing was characterized using optical microscopy, ultraviolet–visible spectroscopy (UV–VIS), attenuated total reflectance-fourier transform infrared (ATR-FTIR) technique, pyrolysis-gas chromatography mass spectrometry (Py-GCMS) together with thermo-gravimetric analysis (TGA), and X-ray photoelectron spectroscopy (XPS). In microscopic observation, most crazes were distributed horizontally rather than vertically from the front of the light aircraft. The horizontally crazed sizes in micrometers are much longer and wider than the vertically crazed sizes. The crazed width at the center region is much larger than that at both tips, showing the close relation with the crazing growth process. In the chemical analysis, the results showed that in the crazed regions ester pendant groups (COOCH3 ) and partial or continuous monomers [CH = C(CH3 )COOCH3 ] from the main chain could be cleaved by chain scissions via photolysis. Thus, polymers with several types of CC double bonds, volatile monomers, and small amount of tertiary alcohols were produced. From these results, we suggested numerous voids (defects) by chain scissions in nanometers probably functioned as the initial points of crazing and crazes continued to grow symmetrically from the starting points to both tips in micrometers under the repeated action of thermal expansion and compression before rupture. These crazes proceeded in the same two aligned directions as the internal tension stress formed during the canopy manufacturing process. This study explains that the combined and synergistic interaction of crazing and environmental stress iteratively occurred on the outer surface of the PMMA canopy through prolonged exposure to tropical climates, finally resulting in the severe crazing.